64 slice-coronary computed tomography sensitivity and specificity in the evaluation of coronary artery bypass graft stenosis: A meta-analysis. (1st August 2016) - Barbero, Umberto; Iannaccone, Mario; d'Ascenzo, Fabrizio; Barbero, Cristina; Mohamed, Abdirashid; Annone, Umberto; Benedetto, Sara; Celentani, Dario; Gagliardi, Marco; Moretti, Claudio; Gaita, Fiorenzo
Abstract: A non-invasive approach to define grafts patency and stenosis in the follow-up of coronary artery bypass graft (CABG) patients may be an interesting alternative to coronary angiography. 64-slice-coronary computed tomography is nowadays a diffused non-invasive method that permits an accurate evaluation of coronary stenosis, due to a high temporal and spatial resolution. However, its sensitivity and specificity in CABG evaluation has to be clearly defined, since published studies used different protocols and scanners. We collected all studies investigating patients with stable symptoms and previous CABG and reporting the comparison between diagnostic performances of invasive coronary angiography and 64-slice-coronary computed tomography. As a result, sensitivity and specificity of 64-slice-coronary computed tomography for CABG occlusion were 0.99 (95% CI 0.97–1.00) and 0.99 (95% CI: 0.99–1.00) with an area under the curve (AUC) of 0.99. 64-slice-coronary computed tomography sensitivity and specificity for the presence of any CABG stenosis > 50% were 0.98 (95% CI: 0.97–0.99) and 0.98 (95% CI: 0.96–0.98), while AUC was 0.99. At meta-regression, neither the age nor the time from graft implantation had effect on sensitivity and specificity of 64-slice-coronary computed tomography detection of significant CABG stenosis or occlusion. In conclusion 64-slice-coronary computed tomography confirmed its high sensitivity and specificity in CABG stenosis or occlusion evaluation. Highlights: 64-slice-CCT permits an accurate evaluation of by-pass grafts. Sensitivity and specificity of 64-slice-CCT are very high for by-pass occlusion and stenosis detection. Neither the age nor the time from graft implantation affects sensitivity and specificity of 64-slice-CCT.